Determinan Kekurangan Energi Kronik (KEK) Remaja Puteri di Lokus Stunting Sulawesi Selatan - Sugirah Nour Rahman; Ryska, Hasra; Irma, Irma; Hadju, Veni (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2025)
Problem of malnutrition in adolescents is chronic energy deficiency (CED) which will have an impact on increasing the prevalence of stunting in infants. This study aims to determine of chronic energy deficiency on adolescent girls. Type of research in this study is an observational cross sectional study in 40 villages of locus stunting Bone and Enrekang involving adolescent girls with cluster random sampling. The instruments of this study is an interview software application on Android and anthropometric measurements of adolescent girls. The dependent variable was CED. The independent variables were age, nutritional knowledge, family income, eating Habits, food Taboo and family smoking status. Data were analysed using the chi-square statistical test to show the relationship between variables. The majority of respondents were in the KEK nutritional status in Bone (56.4%) and Enrekang (51.9%). In Bone and Enrekang regencies, the age group was a determining factor for KEK (p<0.05). Family income in Bone showed significant relationship with the nutritional status of adolescent girls (p<0.05). The nutritional status of adolescent girls is important to pay attention to because they, as future mothers, must have good nutrition to give birth to a quality generation.